2018
DOI: 10.1155/2018/1952685
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Outcomes of Percutaneous Transluminal Renal Angioplasty in Patients with Renal Artery Stenosis: A Retrospective Analysis of 50 Consecutive Cases

Abstract: Background The results of recent trials have brought some confusion to the treatment strategy for renal artery stenosis (RAS). To evaluate the applicability of percutaneous transluminal renal angioplasty (PTRA) for RAS, we extracted the factors that may affect the effectiveness of PTRA from cases experienced at a hypertension center. Methods and Results We retrospectively assessed the blood pressure (BP) lowering effects and renoprotective effects in 50 consecutive patients that had hemodynamically significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…CIN is a major complication of catheter interventions. The most effective method to prevent CIN is to reduce the amount of contrast medium; however, it is di cult to reduce the amount of contrast medium in normal angiography (12,15,16); the average volume of iodinated contrast medium used in the previous studies was approximately 100 mL. Some studies have proposed that carbon dioxide (CO 2 ) can be used as a safe and effective contrast medium, however, the recent CO 2 angiography registry reported a mortality rate of 2% (2/100) (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CIN is a major complication of catheter interventions. The most effective method to prevent CIN is to reduce the amount of contrast medium; however, it is di cult to reduce the amount of contrast medium in normal angiography (12,15,16); the average volume of iodinated contrast medium used in the previous studies was approximately 100 mL. Some studies have proposed that carbon dioxide (CO 2 ) can be used as a safe and effective contrast medium, however, the recent CO 2 angiography registry reported a mortality rate of 2% (2/100) (18).…”
Section: Discussionmentioning
confidence: 99%
“…The most effective way to prevent CIN is to reduce the contrast medium volume; however, it is difficult to do so in normal angiography. 12,15,16 The average volume of iodinated contrast medium used in previous studies was approximately 100 mL. Some studies proposed that carbon dioxide (CO 2 ) can be a safe and effective contrast medium 17 ; however, it is often difficult to evaluate the abdominal area due to abdominal gas.…”
Section: Discussionmentioning
confidence: 99%
“…71 As such, it may guide patients' selection to PTRA. In fact, high RRI (RRI >0.8) suggests advanced parenchymal fibrosis and increased aortic stiffness and has been associated to a lower response to PTRA in most 34,[72][73][74] though not all 75 studies. Finally, while patients with advanced nephropathy (proteinuria >1 g/d or long duration of renal replacement therapy, proteinuria, and prolonged hypertension) are unlikely to benefit from PTRA, 76,77 Murphy et al 78 demonstrated that patients with mild or absent albuminuria may benefit more from blood flow restoration, both in terms of event-free survival, overall survival, cardiovascularrelated death, and progressive renal insufficiency.…”
Section: Are There Specific Subsets Of Patients Who May Potentially B...mentioning
confidence: 99%